AN ANALYSIS OF THE TRANSLATION OF IDIOMS IN "TUESDAY WITH MORRIE" A NOVEL WRITEN BY MITCH ALBOM - Leni Yuliani, - (2009)
This research paper is entitled "An analysis of the translation of idioms in "Tuesdays with Morrie", a novel written by Mitch Albom." The aims of this study were to find out the idioms in the novel 'Tuesdays with Morrie' and the translation strategies used by the translator in translating the idioms. The descriptive qualitative method was used by the writer in analyzing the data. Data consist of a hundred sentences that contain idioms. The data were taken by random sampling method. From the research findings, five types of idioms were found in the novel. They were classified based on Eric Denoun's classifications. They were lexemic idioms, phraseological idioms, one-word idioms, idiomatic pairs, and proverbial idioms. It was apparent that lexemic idioms were the most frequent type of idioms used in the novel. In accordance with Baker's translation strategies, paraphrase strategy is the most frequent translation strategy applied by the translator in translating the idioms. The other three kinds translation strategies used were translation by using an idiom of similar meaning but dissimilar form, translation by using an idiom of similar meaning and form, and translation by omission.